como fazer essa equação :
2 (x+1) -3(2x-5)=6x-3
clareada:
2x + 2 -6x +5=6x-3
Respostas
respondido por:
2
2 (x + 1) - 3 (2x - 5) = 6x - 3
2x + 2 - 6x - 15 = 6x - 3
2x - 6x - 6x = -3 -2 + 15
-10x = 10
x = 10 / -10
x = -1
2x + 2 - 6x - 15 = 6x - 3
2x - 6x - 6x = -3 -2 + 15
-10x = 10
x = 10 / -10
x = -1
respondido por:
1
2(x+1)-3(2x-5)=6x-3
2x+2-6x+15=6x-3
2x-6x-6x=-3-2-15
-10x=-20
x=-20/-10
x=2
2x+2-6x+15=6x-3
2x-6x-6x=-3-2-15
-10x=-20
x=-20/-10
x=2
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás